2020
DOI: 10.1016/j.quaint.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

ESR and ESR/U-series chronology of the Middle Pleistocene site of Tourville-la-Rivière (Normandy, France) - A multi-laboratory approach

Abstract: Tourville-la-Rivière (Normandy, France) is one of the rare Middle Pleistocene palaeoanthropological localities of Northern France. Electron Spin Resonance (ESR) and combined ESR/U-series dating methods were independently applied by different teams on sediments and teeth from this site. The present work provides an overview of this multi-laboratory dating work by integrating a description and discussion of the methodologies employed and results obtained. Results confirm that the ESR/U-series analyses of the tee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Such deviation is however less important for ARD 1801 and 1802 samples which yield similar Al and Ti-Li ages within the range of 1 sigma SD. The high bleaching rates affecting all the T3 samples leads to probable age overestimation of the Al centers 27 , 48 , which makes them unreliable for dating the T3 level (See Supplementary Information, Dating section) and should be considered as maximum age estimations. Nevertheless, Ti-Li centers indicate an effective bleaching rate and can be considered reliable for dating purpose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such deviation is however less important for ARD 1801 and 1802 samples which yield similar Al and Ti-Li ages within the range of 1 sigma SD. The high bleaching rates affecting all the T3 samples leads to probable age overestimation of the Al centers 27 , 48 , which makes them unreliable for dating the T3 level (See Supplementary Information, Dating section) and should be considered as maximum age estimations. Nevertheless, Ti-Li centers indicate an effective bleaching rate and can be considered reliable for dating purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the quartz-rich component of the Ardèche river sediments 19 , 21 , 22 , we used paleodosimetric methods (Electron Spin Resonance – ESR) to date the river deposits 23 27 . In cave environment, radiometric analyses (Uranium series – U-series) are used to date the speleothems growth phases 28 – 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The scatter in ages for the sandy units is thought to result from incomplete resetting of the Al center, but it seems that both the Ti-Li and Al centers for all three units were incompletely reset due to the nature of the fluvial deposition. In contrast, the Ti-H center ESR ages are in agreement with the US-ESR ages of fossil teeth, illustrating its potential for dating late Middle Pleistocene deposits ( 24 ). Unlike luminescence, where single-grain analysis can assess whether sediments have been heterogeneously bleached at deposition ( Section 2.2.1 ), ESR measurements typically need 150 to 200 mg of purified quartz per measurement, and in total, 1 to 2 g may be needed; therefore, this approach is not possible.…”
Section: Trapped Charge Dating Methodsmentioning
confidence: 52%
“…Nevertheless, many archaeological sites have been dated using these multiple quartz ESR signals, such as the earliest Acheulian sites across northwestern Europe ( 22 ), including the French site of Moulin Quignon at 670 to 650 ka ( 23 ). However, the complexity involved in applying ESR (with issues of incomplete resetting of the signal and signal instability) is illustrated by the work at Tourville-la-Rivière, France ( 24 ). Reproducible ages (∼330 ka) were obtained for a silty–clayey sedimentary unit, while two sandy units showed ages ranging from ∼250 ka to more than 1.2 Ma.…”
Section: Trapped Charge Dating Methodsmentioning
confidence: 99%
“…In accordance with the MC approach, ESR age results were calculated for the Al, Ti (option D), and Ti-H (option C) centers (Table 5). Indeed, recent works showed that option D can provide overall accurate results for Early to Late Middle Pleistocene fluvial deposits (e.g., [66][67][68][69][70][71]), while option C (Ti-H) is usually more appropriate over a younger time range, from the Late Middle to Late Pleistocene [58,72]. However, because we are aware of the existing variability within the community regarding how the ESR intensity of Ti centers is measured [73], we also provide the D E estimates of the Ti center derived from options A and E (Supplementary Table S1).…”
Section: Esr Age Calculationmentioning
confidence: 99%